Contagion effect of seasonality in the ASEAN Plus 3 equity markets - Ruzita Abd. Rahim,; Abu Hassan Shaari Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2007)
This study investigates the presence of contagion effect of seasonality in the ASEAN plus 3 markets. The study employs the month-end closing prices of each market's broad based stock indexes over the period of 20 years from January 1987 to December2006, The analysis begins by establishing evidence of seasonality effect in sample markets. Using Granger causality approach, the study finds evidence of causal linkages with Hong Kong and Korea prevailing as leaders to the other ASEAN markets. The timeseries regression analysis confirms that these markets, particularly Korea, have contagion effect on stock returns in Singapore and Malaysia. The study further investigates for the causal linkages due specifically to seasonality effect. Consistent with the results in the general market conditions, Korea remains the leader market in the ASEAN region as well as Hong Kong. Overall, the results lend strong support to the view that seasonality effect in some stock markets is contagious. Specifically, seasonality in Malaysia, Indonesia as well as Hong Kong can be significantly predicted by similar trends in Korea. However, in predicting , seasonality in Singapore, the contagion efect from Malaysia and Indonesia are even more significant than that from Korea. From investment standpoint, the findings imply that investors in these affected (follower) markets should observe the trends in the leader markets in order to improve their chance to exploit the seasonality effect.